(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Problems and errors in the application of computer technologies, Models and methods of organizing software development, the system of equations is solved by the method of a system of linear equations, and unknown phenomena are detected. The decision-making process often has to deal with problems that are often multidimensional in nature.